Students’ Perception of the CoI-based Online Flipped Approach: Learning Mandarin as a Foreign Language - Kuan, Wee Ling (Human Behavior, Development and Society, 2022)
The Community of Inquiry (CoI) framework and the online flipped learning approach have both been extensively investigated as effective instructional designs in online courses; however, there has been little discussion on CoI-based online flipped-Mandarin as a foreign language learning. In this study students’ perception of the CoI-based online flipped MFL learning was examined together with the relationship among teaching presence, cognitive presence, and social presence in online flipped MFL learning. In this study a non-experimental research design and convenience sampling were employed. Data were collected using the CoI questionnaire, which was distributed to 103 full-time undergraduate students enrolled in elementary MFL courses. Descriptive results revealed that design and organization in the teaching presence featured the most; meanwhile, group cohesion in the social presence featured the least. Pearson’s correlation test results showed that a significant relationship existed among the three variables (teaching, cognitive, and social presence), with a particularly strong and positive correlation between the cognitive and social presence. These findings could help shape a new pedagogical design and improve online teaching practices.